Enhancing population-level research among people who inject drugs: a validation and retrospective cohort study using health administrative data in Ontario, Canada - Zoë R Greenwald; Jordan J Feld; Dan Werb; Peter C Austin; Samantha Drover; Daniel Fridman; Ahmed Bayoumi; Tara Gomes; Claire E Kendall; Lauren Lapointe-Shaw; Ayden I Scheim; Sofia R Bartlett; et al. (International Journal of Population Data Science, 2024)
Objective Health administrative data can support population-level research among people who inject drugs (PWID), however these data sources remain underutilized due to the difficulty in identifying drug use in routinely collected data. We validated case-ascertainment algorithms to identify PWID and tested their application in a hepatitis C (HCV) cohort in Ontario, Canada.